2022
DOI: 10.1111/tmi.13781
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in rural Zambia before and during the COVID‐19 pandemic

Abstract: Objectives: With the emergence of the COVID-19 pandemic, restrictions were implemented globally to control the virus. Data on respiratory pathogens in sub-Saharan Africa during the COVID-19 pandemic are scarce. This analysis was conducted to evaluate patterns of respiratory pathogens in rural Zambia before and during the first year of the pandemic. Methods: Surveillance was established in December 2018 at Macha Hospital in southern Zambia. Patients with respiratory symptoms in the outpatient and inpatient clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…In Canada, the average weekly positivity rate for influenza A in 2020-2021 was 0.012% compared to 10.40% in pre-pandemic years, and 0.006% for influenza B compared to 2.60% in pre-pandemic years 1 . Data from other African countries are scarce, with influenza and RSV reductions observed in South Africa and Zambia 13,14 , but not in the Democratic Republic of the Congo (5.6% influenza A positivity and 0.9% influenza B positivity Dec 2020 -March 2021) 15 . Interestingly, the reduction in RSV and influenza in Zambia during the first year of the COVID-19 pandemic was accompanied by increases in rhino/enteroviruses, seasonal coronaviruses, parainfluenza viruses and human metapneumovirus 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the average weekly positivity rate for influenza A in 2020-2021 was 0.012% compared to 10.40% in pre-pandemic years, and 0.006% for influenza B compared to 2.60% in pre-pandemic years 1 . Data from other African countries are scarce, with influenza and RSV reductions observed in South Africa and Zambia 13,14 , but not in the Democratic Republic of the Congo (5.6% influenza A positivity and 0.9% influenza B positivity Dec 2020 -March 2021) 15 . Interestingly, the reduction in RSV and influenza in Zambia during the first year of the COVID-19 pandemic was accompanied by increases in rhino/enteroviruses, seasonal coronaviruses, parainfluenza viruses and human metapneumovirus 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, HAdV has been less impacted by the implementation and easing of public health measures during the COVID-19 pandemic: a Zambian study reported HAdV being identified at higher rates from nasopharyngeal samples throughout the 2020-2021 period of the COVID-19 pandemic, compared to before the pandemic [ 21 ]. Interestingly, this heightened presence of adenovirus was observed a year into the pandemic rather than in its early stages [ 22 ], suggesting a nuanced temporal dynamic that may be related to the virus gradually occupying a specific ecological niche [ 23 , 24 ].…”
Section: Transmissionmentioning
confidence: 99%
“…Limited data are available from sub-Saharan Africa, despite children and adults in this region experiencing significant morbidity and mortality from respiratory infections [5] . Surveillance from South Africa and Zambia reported decreases in influenza viruses and RSV following implementation of public health measures in 2020 [6 , 7] , but to date no studies have reported trends for respiratory infections following easing of restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance is ongoing, thereby providing the opportunity to compare the respiratory pathogen landscape before and during the COVID-19 pandemic in this area. The objective of this analysis was to evaluate the burden and patterns of respiratory viruses in rural Zambia in 2021 compared to previously reported data from 2019 and 2020 [7 , 8] .…”
Section: Introductionmentioning
confidence: 99%